2009
DOI: 10.1534/genetics.109.103036
|View full text |Cite
|
Sign up to set email alerts
|

Precise Gene-Dose Alleles for Chemical Genetics

Abstract: Modulating gene dose is an effective way to alter protein levels and modify phenotypes to understand gene function. In addition, combining gene-dose alleles with chemical perturbation can provide insight into drug-gene interactions. Here, we present a strategy that combines diverse loss-of-function alleles to systematically modulate gene dose in Saccharomyces cerevisiae. The generated gene dosage allele set expands the genetic toolkit for uncovering novel phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…To further support this conclusion, we also found that the greatest degree of MTX sensitivity was achieved when two copies of wild-type SEC21 were expressed in cells ( Figure 5 ). These are consistent with SEC21 representing an indirect target of MTX that nonetheless can confer robust drug resistance in a gene dosage-dependent manner, similarly to DFR1 target ( Yan et al 2009 ).…”
Section: Resultssupporting
confidence: 82%
“…To further support this conclusion, we also found that the greatest degree of MTX sensitivity was achieved when two copies of wild-type SEC21 were expressed in cells ( Figure 5 ). These are consistent with SEC21 representing an indirect target of MTX that nonetheless can confer robust drug resistance in a gene dosage-dependent manner, similarly to DFR1 target ( Yan et al 2009 ).…”
Section: Resultssupporting
confidence: 82%
“…A more inclusive collection of bar-coded yeast strains containing both essential and nonessential genes with decreased abundance of mRNA perturbation (DAmP) is also available to study chemical genetics [ 66 ]. Using this approach, it was shown that the protein product of IPP1 genes, a cytoplasmic inorganic pyrophosphatase is specifically inhibited by NaF [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Use of heterologous constructions where one could adjust the promoter strength would provide the most conclusive data. A possible strategy would be to build upon a recently published protocol [54] which combines diverse loss-of-function alleles, to systematically modulate gene dosage in budding yeast. The use of this protocol on four enzyme-coding genes supports that [0 0 0] is a default sign motif [54] .…”
Section: Discussionmentioning
confidence: 99%